2020
DOI: 10.1177/0886260520925789
|View full text |Cite
|
Sign up to set email alerts
|

Are College Students’ Attitudes Related to Their Application of Sanctions for Campus Sexual Assault Cases?

Abstract: With growing attention to adjudication of campus sexual assault cases, more is known regarding students’ views of sexual assault, but little the literature focuses on how students perceive “justice” in terms of assigning sanctions or guilt/responsibility for such cases. The present study focused on understanding whether college students’ preformed attitudes and beliefs were associated with the severity of sanctions they applied across a range of sexual assault cases as well as their assignments of guilt and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Right-wing authoritarians are more likely to adhere to social conventions, submit to authority, dislike individuals whose identity is not viewed as mainstream and react aggressively toward members of an outgroup (Altemeyer, 1988). In relation to juror behavior, whilst studies have demonstrated RWA individuals to be more prone to convicting defendants for most types of crimes (Devine and Caughlin, 2014; Cramer et al , 2013; Fodor et al , 2008; Jones et al , 2015; Narby et al , 1993), evidence suggests that this relationship is not applicable to cases of sexual victimization offenses (Bhattacharya and Stockdale, 2016; Chahal et al , 2022). Other studies suggest that individuals with high RWA are more likely to place greater blame on victims of sexual offenses (Canto et al , 2021; Spaccatini et al , 2019).…”
Section: Right-wing Authoritarianismmentioning
confidence: 99%
“…Right-wing authoritarians are more likely to adhere to social conventions, submit to authority, dislike individuals whose identity is not viewed as mainstream and react aggressively toward members of an outgroup (Altemeyer, 1988). In relation to juror behavior, whilst studies have demonstrated RWA individuals to be more prone to convicting defendants for most types of crimes (Devine and Caughlin, 2014; Cramer et al , 2013; Fodor et al , 2008; Jones et al , 2015; Narby et al , 1993), evidence suggests that this relationship is not applicable to cases of sexual victimization offenses (Bhattacharya and Stockdale, 2016; Chahal et al , 2022). Other studies suggest that individuals with high RWA are more likely to place greater blame on victims of sexual offenses (Canto et al , 2021; Spaccatini et al , 2019).…”
Section: Right-wing Authoritarianismmentioning
confidence: 99%